Dinosaurs and Ancient Civilizations: Reflections on the Treatment of Cancer - Alnawaz Rehemtulla (Neoplasia: An International Journal for Oncology Research, 2010)
Research efforts in the area of palaeopathology have been seen as an avenue to improve our understanding of the pathogenesis of cancer. Answers to questions of whether dinosaurs had cancer, or if cancer plagued ancient civilizations, have captured the imagination as well as the popular media. Evidence for dinosaurian cancer may indicate that cancer may have been with us from the dawn of time. Ancient recorded history suggests that past civilizations attempted to fight cancer with a variety of interventions. When contemplating the issuewhy a generalized cure for cancer has not been found, it might prove useful to reflect on the relatively limited timethat this issue has been an agenda item of governmental attention as well as continued introduction of an every evolving myriad of manmade carcinogens relative to the total time cancer has been present on planet Earth. This article reflects on the history of cancer and the progress made following the initiation of the “era of cancer chemotherapy.”